The Use of Rhinomanometry in Mouth Breathing: A Systematic Review of the Literature - Castellanos, Merly Fernanda Illera; Silva, Hilton Justino da; Moura, Silvio Ricardo Couto de; Fontes, Luciana de Barros Correia; Lima, Niedje Siqueira de; Bezerra, Thiago Freire Pinto; Cunha, Daniele Andrade da (International Archives of Otorhinolaryngology, 2024)
Introduction Mouth breathing generates imbalances in the musculature, in craniofacial morphofunctionality, and in the stomatognathic system. Therefore, it is essential to make a diagnosis of mouth breathing through the quantitative assessment of nasal permeability, which can be performed through rhinomanometry.Objective To investigate the effectiveness of rhinomanometry in the diagnosis of mouth breathing in pediatric patients through a systematic review of the literature.Data synthesis The guiding question was: “Is the use of rhinomanometry as an assessment tool effective in the diagnosis of mouth breathing in pediatric patients?”. We conducted a search on the following databases: Latin American and Caribbean Center on Health Sciences Information (BIREME), Latin American and Caribbean Health Sciences Literature (LILACS), PubMed/Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (SciELO), Web of Science, and Science Direct. The Health Sciences Descriptors (Descritores em Ciências da Saúde, DECS, in Portuguese) and Medical Subjects Headings (MESH) were combined with the Boolean operator AND in the search strategy: rhinomanometry AND mouth breathing AND diagnosis AND nasal pressure AND nasal airflow AND nasal resistance. Observational cohort and cross-sectional studies that addressed the effectiveness of rhinomanometry in the diagnosis of mouth breathing were included. The reviewers independently extracted the information and scored the review quality based on the Physiotherapy Evidence Database (PEDro) scale and the grading of evidence levels according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Of the 1,536 articles identified, only 3 were selected for the present review after the application of the eligibility criteria.Conclusion There is great concern regarding the assessment of nasal function. There was a lack of standardization of rhinomanometry to test the effectiveness of nasal resistance as an aid in the diagnosis of breathing mode.
Keywords: rhinomanometry; airway resistance; mouth breathing